Stuffing the refugee education pipeline: the integration process and the exclusion of refugees from knowledge production in a Western destination country - Abamosa, Juhar Yasin (Frontiers in Education, 2024)
The number of forcibly displaced people, including refugees, has been increasing exponentially over the last few decades. Refugees settled in Western destination countries face several challenges in successfully accessing and participating in higher education and in becoming knowledge producers. This is in sharp contrast to uncritical assumptions that refugees settled in these countries are better off in terms of pursing higher education. To shed more light on this issue, I aim to address the research question ‘How does the integration process in a Western destination country contribute to the exclusion of refugees from knowledge production?’ The article uses an education pipeline analogy and human agency theory as the theoretical framework. I conduct narrative interviews with six refugees who planned to pursue higher education but could not realise their plans in Norway. The findings indicate that the refugee education pipeline is broken and stuffed with various restrictive factors that weaken the refugees’ agency to make informed decisions. These factors included a long waiting time for settlement, withholding relevant information about higher education, demotivating and misplaced advice about higher education and language training programmes for non-academic purposes. The article ends with a conclusion and several implications.